PHYLOGENY AND HOST SPECIFICITY OF KIDNEY INFECTING MYXIDIUM SPECIES - Baiko, Dariya (Jihočeská univerzita, 2017)
The focus of this Bachelor thesis was to determine the phylogenetic position of Myxidium rhodei Leger 1905, a common kidney-infecting myxosporean parasite of Eurasian cyprinid fish. Host specificity of M. rhodei was investigated by light microscopy and PCR screening with subsequent DNA sequencing.
PHYLOGENY AND HOST SPECIFICITY OF KIDNEY INFECTING MYXIDIUM SPECIES
Keywords: Myxozoa; Myxidium rhodei; phylogeny; host specificity; kidney; cyprinid fish; Myxozoa; Myxidium rhodei; phylogeny; host specificity; kidney; cyprinid fish